Strategi Dakwah Ustadz Abu Deedat Syihab dalam Upaya Mengantisipasi Gerakan Kristenisasi di Indonesia - Ana Safiana; Sunaryanto (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
This research was conducted to understand the da'wah strategies used by Ustadz Abu Deedat Syihab in anticipating Christianization movements in Indonesia. This research focuses on the strategies, approaches, and da'wah activities used, as well as their impact on the Muslim community in Indonesia, particularly in handling apostasy cases.The research method used in this study is qualitative descriptive with a social anthropological approach. This research is qualitative because it collects data through interview methods, observation, literature study, and documentation. The results of this research discussion show that Christianization in Indonesia has covered all aspects of life, from education, health, culture, social, politics, and economics. They approach communities based on field research they conduct before carrying out their mission, not just based on mere assumptions, but implemented with precise targeting. Additionally, the destruction of the morality of Muslims by Christian missionaries has also achieved remarkable results. They create fortresses that isolate and manipulate Islam from most Indonesians so that Muslims doubt their own religion. Christianization in Indonesia has different views regarding joint decisions about socializing religious ethical codes. The Christianization campaigns conducted by missionaries in Indonesia have crossed boundaries and do not comply with the ethics of religious propagation. Therefore, the author researched the da'wah strategies used by Ustadz Abu Deedat Syihab as an Indonesian Christology figure in efforts to anticipate the Christianization Movement.